(untitled) (TAJDID: Jurnal Ilmu Ushuluddin, 2023)
The discourse of eschatology is still an interesting topic among scholars. In Indonesia, the issue of eschatology and the works that discuss it experienced significant development from the 1990s to the early 2000s, especially during the transition from the New Order government era to reformation. One of the important figures in the delivery of a distinctive and unique eschatology is Maimun Zubair through Safinah Kalla Saya’lamun fi Tafsir Shaykhina Maymun. This work originated from the study of Tafsir Al-Jalalayn every Sunday at Pesantren Al-Anwar Sarang which was collected by Ismail al-Ascholy. Its contextual approach and relevance to the contemporary context has made the concept of eschatology easier to understand by the community. This article aims to review the contextualization of the interpretation of eschatological verses in Safinah Kalla Saya’lamun fi Tafsir Shaykhina Maymun. The research method used is library research and content analysis. Using a sociology of knowledge approach, the results of this study show that Maimun Zubair firmly states that eschatology is not only a prediction of the future to come, but has occurred in the midst of the contemporary era. This is an interesting view and different from other interpretations, both from classical, modern, and Nusantara interpretations that still maintain a more literal interpretation. This work is significant for portraying the role of pesantren clerics such as Maimun Zubair in trying to bridge religious understanding with real life, thus providing valuable guidance for Muslim communities in facing changing times. Maimun Zubair also succeeded in bringing together diverse sources of thought, combining intellectuals from the Middle East and Indonesia with harmonious synergy Diskursus eskatologi masih menjadi topik menarik di kalangan para sarjana. Di Indonesia, isu eskatologi dan karya-karya yang membahasnya mengalami perkembangan siginifikan sejak dekade 1990-an hingga awal 2000-an, terutama selama masa transisi dari era pemerintahan Orde Baru menuju reformasi. Salah satu tokoh penting dalam penyampaian eskatologi yang khas dan unik adalah Maimun Zubair melalui tafsir Safinah Kalla Saya‘Lamun fi Tafsir Shaykhina Maymun. Karya ini berawal dari kajian Tafsir Al-Jalalayn setiap hari ahad di Pesantren Al-Anwar Sarang yang dikumpulkan oleh Ismail al-Ascholy. Pendekatannya yang kontekstual dan relevan dengan konteks kontemporer telah membuat konsep eskatologi menjadi lebih mudah dipahami oleh masyarakat. Artikel ini bertujuan untuk mengulas kontekstualisasi penafsiran ayat-ayat eskatologi dalam tafsir Safinah Kalla Saya‘lamun fi Tafsir Shaykhina Maymun. Metode penelitian yang digunakan adalah library research dan content analysis. Dengan menggunakan pendekatan sosiologi pengetahuan, hasil penelitian ini menunjukkan bahwa Maimun Zubair dengan tegas menyatakan bahwa eskatologi tidak hanya merupakan ramalan masa depan yang akan datang, tetapi telah terjadi di tengah-tengah era kontemporer. Ini adalah pandangan yang menarik dan berbeda dengan tafsir lain, baik dari tafsir klasik, modern, maupun Nusantara yang masih menjaga interpretasi yang lebih literal. Karya ini signifikan untuk memotret peran kiai pesantren seperti Maimun Zubair berusaha menjembatani pemahaman agama dengan kehidupan nyata, sehingga memberikan panduan yang berharga bagi masyarakat Muslim dalam menghadapi perubahan zaman. Maimun Zubair juga berhasil menyatukan beragam sumber pemikiran, menggabungkan intelektualitas dari Timur Tengah dan Indonesia dengan sinergi yang harmonis.